2013
DOI: 10.4103/0970-9185.111727
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of research in anesthesia: Culmination into publication?

Abstract: Background:To assess the quality of research presentations made in conferences, its success or failure to be published in a peer-reviewed journal is a well-accepted marker. However, there is no data regarding the publication of research presentations made in Indian conferences of anesthesiology.Objective:The primary objective was to determine publication rate of research presented at the largest and best attended national conference in anesthesiology, the Indian Society of Anaesthesiologists’ Conference (ISACO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
0
23
1
Order By: Relevance
“…A Cochrane review on the topic showed the publication rate of presentations at International meetings to be 44.5 %. However, all/ most studies included in the meta-analysis were from international conferences, which have been recently shown to have a higher subsequent full publication rate [11]. A previous systematic review [12] had also reported a similar (51 %) fullpublication rate, suggesting that there has not been much change in this proportion over recent times.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A Cochrane review on the topic showed the publication rate of presentations at International meetings to be 44.5 %. However, all/ most studies included in the meta-analysis were from international conferences, which have been recently shown to have a higher subsequent full publication rate [11]. A previous systematic review [12] had also reported a similar (51 %) fullpublication rate, suggesting that there has not been much change in this proportion over recent times.…”
Section: Discussionmentioning
confidence: 91%
“…A pediatric study from UK reported up to 78 % publication rate after an interval of three years of two general pediatric conferences [7], whereas nearly 30 % of abstracts at an African pediatric surgery conference were published during a 2-6 y period [10]. A more recent Indian study form an Anesthesia conference showed a publication rate of only 5 % after two years of presentation, and only 58 % of these were in indexed journals [11]. A Cochrane review on the topic showed the publication rate of presentations at International meetings to be 44.5 %.…”
Section: Discussionmentioning
confidence: 94%
“…Our study included the most comprehensive national meeting about Anesthesiology and Intensive Care in which nearly 1500 participants attend annually in Turkey. Similarly, in the same field report from in The Indian Society of Anaesthesiologists national congress that is the primary conference of anesthesia in India the publication rate of presentations was 5% [15]. No similar studies were found in Turkey about Anaesthesiology and Reanimation, but when different clinical branches were compared, our rate is relatively lower than those presented at national congress for clinical specialties held in Turkey and other countries [3][4][5]16].…”
Section: Resultsmentioning
confidence: 59%
“…
AbstractAim: This study aimed to determine the rate of conversion to scientific publication of abstracts presented at the annual congress of Turkish Society of Anesthesia and Reanimation (TARD) between the period of 2011-2013.Material and Method: The abstracts presented at TARD Congresses in 2011, 2013 and published in various peer-reviewed medical journals were identified using PubMed and Google Scholar. In a retrospective study design, the abstracts were divided into either oral presentations(OP) or poster presentations(PP), type of the study; trial design, first author's name and affiliated institution, mean publication time and journal name were analyzed.Result: From a total of 2417 abstracts, 114(4.7%) were found to be published as a scientific full-text article.

While the conversion rate of OP was; 24 of 187(12.8%), for PP it was 90 of 2230(4%), and the difference was statistically significant (p<0.001).

…”
mentioning
confidence: 99%
“…Twenty-five Indian abstracts were presented at the European Society of Intensive Care Medicine Congress in 2013. However, the publication rate in international journals has been very low [10]. Rejection of manuscripts at peer review could certainly be a major reason, but perhaps time constraints and lack of motivation to publish were important contributing factors.…”
mentioning
confidence: 99%